Transitions to food democracy through multilevel governance - Jani, Anant; Exner, Andreas; Braun, Reiner; Braun, Brigitte; Torri, Luisa; Verhoeven, Sofie; Murante, Anna Maria; Van Devijvere, Stefanie; Harrington, Janas; Ochoa, Amalia; Marchiori, Giorgia Dalla Libera; Defranceschi, Peter; et al. (Frontiers in Sustainable Food Systems, 2022)
Food systems in Europe are largely unjust and not sustainable. Despite substantial negative consequences for individual health, the environment and public sector health and care services, large multi-national corporations continue to benefit from the way food systems are designed—perpetuating “Lose–Lose–Lose–Win” food systems that see these large corporations benefit at the expense of health, the environment and public sector finances. Transitioning to “Win–Win–Win–Win” food systems is challenging because of the heterogeneity, complexity and unpredictable nature of food systems—one-size fits-all solutions to correct imbalances and injustices cannot exist. To address these challenges, we propose the use of heuristics—solutions that can flexibly account for different contexts, preferences and needs. Within food systems, food democracy could be a heuristic solution that provides the processes and can form the basis for driving just transitions. However, ensuring that these transition processes are fair, equitable, sustainable and constructive, requires an approach that can be used across vertical and horizontal governance spheres to ensure the voices of key stakeholders across space, time and spheres of power are accounted for. In this manuscript we outline a new Horizon project, FEAST, that aims to use multilevel governance approaches across vertical and horizontal spheres of governance to realize constructive food democracy. We envisage this as a means to inform just processes that can be used to design and implement policies, in line with food democracy, to facilitate transitions to “Win–Win–Win–Win” food systems across Europe that makes it easy for every European to eat a healthy and sustainable diet.